Abrasion-resistant and acid-alkali-resistant CMP polishing cushion with controllable foam holes and preparation method thereof

By controlling the temperature of the polyurethane slurry and forming a bridged silicone gel layer, the problem of poor controllability of the cell shape and size of the existing CMP polishing pad is solved, and the cell uniformity, wear resistance and acid and alkali resistance are achieved, which extends the service life and reduces costs.

CN119531151APending Publication Date: 2025-02-28WANHUA CHANGZHOU NEW MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411733983.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing CMP polishing pads have poor controllability in the shape and size of the cell during production and use, resulting in unstable polishing quality, uneven material removal rate, short service life, which increases production costs and affects production efficiency.

Method used

By controlling the gentle solidification bath temperature of the polyurethane slurry, a regular and orderly vertical bubble cell is formed, and a bridged silicone gel layer is formed on the surface of the polyurethane coating and the bubble cell to improve the wear resistance and acid and alkali resistance of the polishing pad.

Benefits of technology

The uniformity of cell distribution is achieved, the carrying capacity and grinding stability of polishing liquid are improved, the service life is extended, and the semiconductor manufacturing cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical mechanical polishing, in particular to a cell-controllable wear-resistant acid-alkali-resistant CMP polishing cushion and a preparation method thereof.The preparation method comprises the following steps that S1, after base cloth is soaked in an acid-alkali swing soaking material to be pretreated, the base cloth is coated with polyurethane slurry, and then the base cloth is dried to obtain the cell-controllable wear-resistant acid-alkali-resistant CMP polishing cushion; then immersing the base cloth into a coagulating bath so that the polyurethane slurry on the surface of the base cloth is coagulated to form a polyurethane coating, forming regular and orderly vertical foam holes from the surface of the coating to the interior of the coating, and washing, drying and polishing to obtain a base; s2, soaking the base into the bridging organic silicon sol, taking out, hanging upside down and horizontally standing, drying the sol to form bridging organic silicon gel, washing with water, and drying to obtain the wear-resistant acid and alkali-resistant CMP polishing cushion with controllable cells; the polishing cushion obtained through the method is uniform in foam hole distribution, good in polishing solution carrying capacity and polishing stability and good in abrasion resistance and acid and alkali resistance, and meanwhile the service life can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical mechanical polishing, and in particular to a wear-resistant and acid- and alkali-resistant CMP polishing soft pad with controllable pores and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, the integration of integrated circuits continues to increase, and the requirements for manufacturing processes are becoming more and more stringent. In this context, the performance of polishing pads, as the core components of the CMP process, directly affects the quality and production efficiency of the final product. Chemical mechanical polishing (CMP) technology plays an important role in semiconductor manufacturing, and its related technologies and materials are also constantly developing and improving to meet the increasing requirements of the semiconductor industry. In the past five years, the market size of CMP polishing pads has shown a gradual growth trend. While the market size has grown, technology has also been continuously improving to meet the increasing requirements of the semiconductor industry. Domestic companies are also constantly working on localization substitution in this field and have achieved certain results. However, CMP polishing pad manufacturing technology still faces the challenge of poor controllability of the shape and size of the pores, and continuous technological innovation and optimization are needed.

[0003] Existing polishing pads may have surface defects such as cracks and holes during production or use. These defects will affect the polishing quality. After long-term use, the surface wear is more serious, resulting in uneven material removal rate during polishing, thereby affecting the flattening effect of the entire silicon wafer. In addition, the service life is relatively short and needs to be replaced frequently, which not only increases production costs, but may also affect production efficiency. Summary of the invention

[0004] In view of the above technical problems, a wear-resistant and acid-alkali-resistant CMP polishing pad with controllable pores and a preparation method thereof are provided. The polishing pad obtained by the method of the present invention has uniform pore distribution, good carrying capacity for polishing liquid and polishing stability, good wear resistance, acid and alkali resistance, and can prolong service life.

[0005] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:

[0006] A method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores comprises the following steps:

[0007] S1, soaking the base fabric in the acid-base swing impregnation, taking it out, squeezing it, letting it stand, and coating the polyurethane slurry on the base fabric, and then immersing it in a coagulation bath to solidify the polyurethane slurry on the surface of the base fabric to form a polyurethane coating, and forming regular and orderly vertical bubbles from the surface of the coating to the inside of the coating, and then washing, drying, and polishing to obtain the bass;

[0008] S2. The bridging organosilicon precursor is hydrolyzed and polymerized to obtain a bridging organosilicon sol, and the base is immersed in the bridging organosilicon sol. After being taken out, it is hung upside down and placed horizontally. After the sol is dried, a bridging organosilicon gel is formed on the surface of the polyurethane coating without pores and the inner surface of the pores, and then washed with water and dried to obtain a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores.

[0009] Furthermore, the bridged organosilicon precursor is selected from one or more of 1,2-bis(triethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethylene and 1,3-bis(triethoxysilyl)acetylene.

[0010] Furthermore, in S2, the bridged organosilicon precursor, water and hydrochloric acid are stirred in ethanol at a constant temperature of 35-45°C for 1h-2h for hydrolysis polymerization; wherein the molar ratio of the bridged organosilicon precursor, water and hydrochloric acid is 1:50-60:0.1-0.2.

[0011] Furthermore, the mass fraction of the bridged organic silica sol is 0.1%-2%; the time for which the bass is immersed in the bridged organic silica sol is 5min-10min.

[0012] Further, the acid-base swing soaking material in S1 is selected from an acidic soaking material or an alkaline soaking material, which means a soaking material with a non-fixed pH value;

[0013] The acidic soaking material is a DMF solution containing citric acid, and the mass fraction of the acidic soaking material is in the range of 0%-5%;

[0014] The alkaline impregnation material is a DMF solution containing ammonia water, and the mass fraction of the alkaline impregnation material is in the range of 0%-5%.

[0015] Furthermore, the coagulation bath in S1 is a DMF aqueous solution with a mass fraction of 18%-25%, and the temperature of the coagulation bath is 19-25°C; the coating thickness of the polyurethane slurry is 1mm. Preferably, the coagulation bath is a DMF aqueous solution with a mass fraction of 22%, and the coagulation is performed at a temperature of 23°C.

[0016] Furthermore, after solidification into a film in S1, it is washed with clean water, and then extruded in the range of 1kg-5kg, and the washing-extrusion operation is repeated 40-80 times; the subsequent drying temperature of S1 is in the range of 120℃-150℃, and the drying time is 10min-30min.

[0017] Furthermore, the inverted and horizontal standing in S2 is to lower the polished surface and flatten it horizontally and then stand it for 2-6 minutes; the temperature of the subsequent drying and re-drying in S2 is in the range of 120℃-150℃, and the drying time is 10min-30min; the washing between the two dryings is washed with clean water, and then squeezed in the range of 1kg-5kg, and the washing-squeezing operation is repeated 40-80 times.

[0018] On the other hand, the present invention provides a wear-resistant and acid-resistant CMP polishing pad with controllable pores obtained by the above-mentioned preparation method, whose structure includes a base cloth, a polyurethane coating on the surface of the base cloth, the polyurethane coating surface to the interior thereof has regular and orderly vertical pores, and the surface of the polyurethane coating without pores and the inner surface of the pores have a bridging silicone gel layer.

[0019] Further, the thickness of the polyurethane coating is 0.6mm-0.7mm;

[0020] The length of the pores is in the range of 0.3 mm to 0.7 mm and does not contact the base fabric (ie, a certain thickness is still left between the bottom of the pores and the base fabric); the bottom diameter of the pores is in the range of 0.09 mm to 0.3 mm.

[0021] Beneficial technical effects:

[0022] The present invention controls the length and size of the pores by controlling the temperature of the polyurethane slurry and the coagulation bath, thereby improving the controllability of the pore capacity of the polishing pad, thereby improving the controllability of the polishing pad's carrying capacity for the polishing liquid, and improving the accuracy of polishing; the present invention controls the acidity and alkalinity of the impregnated material to pretreat the base cloth first, and then protonates or deprotonates the polyurethane molecules in the coagulation bath process, controls the interaction force between the molecules, and then controls the polyurethane coagulation speed and the shape of the pores, so that the pores are more evenly distributed, the carrying capacity of the polishing pad for the polishing liquid is improved, and the polishing stability of the polishing pad is improved; the present invention places the bridged organic silicon sol in the pores A bridged silicone gel layer is formed on the surface of the controllable polyurethane synthetic leather and in the pores. Since the bridged silicone has a unique bridged structure with tighter and more stable connections between molecules, and it contains both organic groups and siloxane structures, when it forms a gel and adheres to the surface of the polyurethane and the inner surface of the pores, the organic groups of the bridged silicone make it more compatible with the polyurethane, thereby increasing the wear resistance and stability of the polishing pad. The siloxane part makes the polishing pad more resistant to acids and alkalis, making it less prone to chemical reactions. This improves the wear resistance of the polishing pad while also improving its acid and alkali resistance and extending its service life, thereby further reducing the manufacturing cost of semiconductors. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1The schematic diagram of the cross-sectional structure of the wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores obtained by the method of the present invention is shown. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.

[0025] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0026] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, they are carried out in accordance with general standard requirements or general methods.

[0027] The polyurethane slurry used below has the following formula: DMF 50g, XCW-P80R 100g, black slurry 10g, wherein XCW-P80R is a polyurethane resin for wet synthetic leather, with a solid content of 30wt%, provided by Asahikawa Chemical (Suzhou) Co., Ltd.

[0028] Example 1

[0029] A method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores comprises the following steps:

[0030] S1. Add 2g of citric acid solid to 98g of DMF and stir to completely dissolve the citric acid to obtain an acidic impregnation material. Soak the base fabric (0.2mm peach skin) in the aforementioned acidic impregnation material (completely soaked, no time limit), take it out and squeeze it with 4kg, let it stand for 1min, then coat the 23°C polyurethane slurry on the base fabric with a coating thickness of 1mm, let it stand for 1min, immerse it in a 23°C, 22wt% DMF aqueous solution (i.e., the temperature of the coagulation bath is 23°C) to solidify the polyurethane slurry on the surface of the base fabric to form a polyurethane coating (PU coating), and form regular and orderly vertical bubbles from the surface of the coating to the inside of the coating, wash with clean water and squeeze with 4kg, repeat the washing-squeezing operation 50 times, then dry it at 140°C for 15min and grind off 0.1mm of thickness with 180-mesh sandpaper to obtain a bass;

[0031] S2. Preparation of bridged organosilica sol: add 1 g of 1,2-bis(triethoxysilyl)ethane (0.002820 mol) to 15.94 g of anhydrous ethanol, stir for 1 min, then drop 2.78 g of deionized water (0.1543 mol), continue stirring for 1 min, then drop 0.278 g of 3.7 wt% hydrochloric acid aqueous solution (containing 0.0002821 mol of hydrochloric acid), then immediately transfer to a constant temperature water bath at 40° C. and continue stirring for 2 h to obtain a bridged organosilica sol with a concentration of 5 wt%;

[0032] The 5wt% bridged organosilicon sol obtained above was diluted with anhydrous ethanol to a concentration of 0.5wt%, and the base obtained in S1 was immersed in the 0.5wt% bridged organosilicon sol (immersion time 5min). After being taken out, the polished surface was faced down and laid horizontally and left to stand for 5min, and then dried at 130°C for 10min to form a bridged organosilicon gel on the surface of the polyurethane coating without pores and the inner surface of the pores. After washing with clean water, it was squeezed with 4kg, and the washing-squeezing operation was repeated 50 times. Then, it was dried at 140°C for 15min to obtain a wear-resistant and acid-alkali-resistant CMP polishing pad with controllable pores. The cross-sectional structure of the polishing pad is as shown in FIG. Figure 1 shown.

[0033] Example 2

[0034] A method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores comprises the following steps:

[0035] S1. Add 2g of ammonia water (25wt%) to 98g of DMF and stir evenly to obtain an alkaline impregnation material. Soak the base fabric (same as in Example 1) in the alkaline impregnation material (completely soaked, no time limit), take it out and squeeze it with 4kg, let it stand for 1min, then coat the polyurethane slurry (same as in Example 1) at room temperature of 23°C on the base fabric, the coating thickness is 1mm, let it stand for 1min, immerse it in a DMF aqueous solution at 23°C and a concentration of 22wt% to solidify the polyurethane slurry on the surface of the base fabric to form a polyurethane coating, and form regular and orderly vertical bubbles from the surface of the coating to the inside of the coating, wash with clean water and squeeze with 4kg, repeat the washing-squeezing operation 50 times, then dry it at 140°C for 15min and grind off 0.1mm of thickness with 180-mesh sandpaper to obtain a bass;

[0036] S2. Preparation of bridged organosilica sol: add 1 g of 1,2-bis(triethoxysilyl)ethane (0.002820 mol) to 15.94 g of anhydrous ethanol, stir for 1 min, then drop 2.78 g of deionized water (0.1543 mol), continue stirring for 1 min, then drop 0.278 g of 3.7 wt% hydrochloric acid aqueous solution (containing 0.0002821 mol of hydrochloric acid), then immediately transfer to a constant temperature water bath at 40° C. and continue stirring for 2 h to obtain a bridged organosilica sol with a concentration of 5 wt%;

[0037] The 5wt% bridged organosilicon sol obtained above was diluted with anhydrous ethanol to a concentration of 0.5wt%, and the base obtained by S1 was immersed in the 0.5wt% bridged organosilicon sol (immersion time 5min). After being taken out, it was laid horizontally with the polished surface facing down and left to stand for 5min, and then dried at 130°C for 10min to allow the surface of the polyurethane coating without pores and the inner surface of the pores to form a bridged organosilicon gel. After washing with clean water, it was squeezed with 4kg, and the washing-squeezing operation was repeated 50 times. Then, it was dried at 140°C for 15min to obtain a wear-resistant and acid-alkali-resistant CMP polishing pad with controllable pores.

[0038] Example 3

[0039] A method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores comprises the following steps:

[0040] S1. Add 2g of citric acid solid to 98g of DMF and stir to completely dissolve the citric acid to obtain an acidic impregnation material. Soak the base fabric (same as in Example 1) in the aforementioned acidic impregnation material (completely soaked, no time limit), take it out and squeeze it with 4kg, let it stand for 1min, then coat the 19°C polyurethane slurry on the base fabric with a coating thickness of 1mm, let it stand for 1min, immerse it in a 19°C, 22wt% DMF aqueous solution to solidify the polyurethane slurry on the surface of the base fabric to form a polyurethane coating, and form regular and orderly vertical bubbles from the surface of the coating to the inside of the coating, wash with clean water and squeeze with 4kg, repeat the washing-squeezing operation 50 times, then dry it at 140°C for 15min and grind off 0.1mm of thickness with 180-mesh sandpaper to obtain a bass;

[0041] S2. Preparation of bridged organosilica sol: add 1 g of 1,2-bis(triethoxysilyl)ethane (0.002820 mol) to 15.94 g of ethanol, stir for 1 min, then drop 2.78 g of deionized water (0.1543 mol), continue stirring for 1 min, then drop 0.556 g of 3.7 wt% hydrochloric acid aqueous solution (containing 0.0005636 mol of hydrochloric acid), then immediately transfer to a constant temperature water bath at 40° C. and continue stirring for 1 h to obtain a bridged organosilica sol with a concentration of 5 wt%;

[0042] The 5wt% bridged organosilicon sol obtained above was diluted with anhydrous ethanol to a concentration of 2wt%, and the base obtained by S1 was immersed in the 2wt% bridged organosilicon sol (immersion time 10min). After being taken out, it was laid horizontally with the polished surface facing down and left to stand for 5min, and then dried at 130°C for 10min to allow the surface of the polyurethane coating without pores and the inner surface of the pores to form a bridged organosilicon gel. After washing with clean water, it was squeezed with 4kg, and the washing-squeezing operation was repeated 50 times. Then, it was dried at 140°C for 15min to obtain a wear-resistant and acid-alkali-resistant CMP polishing pad with controllable pores.

[0043] Comparative Example 1

[0044] The preparation of the polishing pad in this case is the same as that in Example 1, except that in S1, there is no operation of treating the base fabric with an acidic immersion material, but the base fabric is directly immersed in pure DMF and then subjected to subsequent operations.

[0045] Comparative Example 2

[0046] The preparation of the polishing pad in this case is the same as that in Example 1, except that in S1, a 15°C polyurethane slurry is used to coat the base fabric, and the temperature of the subsequent coagulation bath is 15°C.

[0047] Comparative Example 3

[0048] The preparation of the polishing pad in this case is the same as that in Example 1, except that in S1, a 27°C polyurethane slurry is used to coat the base fabric, and the temperature of the subsequent coagulation bath is 27°C.

[0049] Comparative Example 4

[0050] The preparation of the polishing pad in this case is the same as that in Example 1, except that the 5 wt % bridging organosilicon sol is not diluted in S2 but is used directly.

[0051] Comparative Example 5

[0052] The preparation of the polishing pad in this case is the same as that in Example 1, except that only S1 is performed and S2 operation is not performed.

[0053] Comparative Example 6

[0054] The preparation of the polishing pad in this case is the same as that in Example 1, except that 0.5 wt % silica sol (neutral, silica particle size 5-20 nm) is used to treat the base in S2, and other operations are the same as S2.

[0055] The measurement results of the wear of the CMP polishing pad, 24h 10wt% NaOH immersion, 24h 5wt% HCl immersion, PU coating thickness, long hole length range, and long hole diameter range are shown in Table 1.

[0056] Table 1 Polishing pad performance of each case

[0057]

[0058]

[0059] As can be seen from Table 1, in combination with Example 1 and Comparative Example 1, it can be seen that when there is no acid-base swing impregnation material (i.e., there is no acidic impregnation material or alkaline impregnation material), the cell length fluctuates greatly and the cells are uneven, which verifies that the acid-base swing impregnation material can control the shape of the cells and make the cells more uniform;

[0060] Combining Example 1 and Comparative Example 2, it can be seen that when the material temperature and the solidification temperature are lower than the optimal temperature range, the pores are short and the length and size are uneven, which verifies that the length and size of the pores can be controlled by controlling the material temperature and the solidification temperature;

[0061] Combining Example 1 and Comparative Example 3, it can be seen that when the material temperature and the solidification temperature are higher than the optimal temperature range, the pores are longer and larger, but the length and size of the pores are uneven, which verifies that more uniform pores can be formed by controlling the material temperature and the solidification temperature within the range of 19 to 25°C;

[0062] Combining Example 1 and Comparative Example 4, it can be seen that when the concentration of the bridging organosilicon sol is too high, the sol will block some of the pores, resulting in a decrease in the wear resistance of the CMP polishing pad, which verifies that an excessively high concentration of the bridging organosilicon sol is not conducive to improving the wear resistance of the CMP polishing pad;

[0063] Combining Example 1 and Comparative Example 5, it can be seen that the polishing pad of Comparative Example 5 has poor wear resistance and is not resistant to acid and alkali, which verifies that the synergistic effect of bridging organic silicon sol and polyurethane synthetic leather with controllable pores can improve the wear resistance and acid and alkali resistance of the polyurethane synthetic leather polishing pad and extend the service life of the polishing pad.

[0064] Combining Example 1 and Comparative Example 6, it can be seen that the silica sol used to treat the base in Comparative Example 6 cannot obtain an effective wear-resistant and alkali-resistant polishing pad, which verifies that the synergistic effect of the bridging organic silicon sol and the pore-controlled polyurethane synthetic leather can improve the wear resistance and acid and alkali resistance of the polyurethane synthetic leather polishing pad and extend the service life of the polishing pad.

[0065] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores, characterized in that: The steps include: S1, soaking the base fabric in the acid-base swing impregnation, taking it out, squeezing it, letting it stand, and coating the polyurethane slurry on the base fabric, and then immersing it in a coagulation bath to solidify the polyurethane slurry on the surface of the base fabric to form a polyurethane coating, and forming regular and orderly vertical bubbles from the surface of the coating to the inside of the coating, and then washing, drying, and polishing to obtain the bass; S2. The bridging organosilicon precursor is hydrolyzed and polymerized to obtain a bridging organosilicon sol, and the base is immersed in the bridging organosilicon sol. After being taken out, it is hung upside down and placed horizontally. After the sol is dried, a bridging organosilicon gel is formed on the surface of the polyurethane coating without pores and the inner surface of the pores, and then washed with water and dried to obtain a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores.

2. The method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores according to claim 1, characterized in that: The bridged organosilicon precursor is selected from one or more of 1,2-bis(triethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethylene and 1,3-bis(triethoxysilyl)acetylene.

3. The method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores according to claim 2, characterized in that: In S2, the bridged organosilicon precursor, water and hydrochloric acid are stirred in ethanol at a constant temperature of 35-45° C. for 1 h-2 h for hydrolysis polymerization; The molar ratio of the bridged organosilicon precursor, water and hydrochloric acid is 1:50-60:0.1-0.

2.

4. The method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores according to any one of claims 1 to 3, characterized in that: The mass fraction of the bridged organic silica sol is 0.1%-2%.

5. The method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores according to claim 4, characterized in that: The acid-base swing soaking material in S1 is selected from an acid soaking material or an alkaline soaking material; The acidic soaking material is a DMF solution containing citric acid, and the mass fraction of the acidic soaking material is in the range of 0%-5%; The alkaline impregnation material is a DMF solution containing ammonia water, and the mass fraction of the alkaline impregnation material is in the range of 0%-5%.

6. The method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores according to claim 5, characterized in that: The coagulation bath in S1 is a DMF aqueous solution with a mass fraction of 18%-25%, and the temperature of the coagulation bath is 19-25° C.; the coating thickness of the polyurethane slurry is 1 mm.

7. The method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores according to claim 5, characterized in that: After solidification in S1, the mixture is washed with clean water, and then extruded within a range of 1kg-5kg, and the washing-extrusion operation is repeated 40-80 times; the subsequent drying temperature in S1 is within a range of 120°C-150°C, and the drying time is 10min-30min.

8. The method for preparing a wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores according to claim 5, characterized in that: The inverted and horizontal standing in S2 is to put the polished surface downward and flatten it horizontally and then stand it for 2-6 minutes; the temperature of the subsequent drying and re-drying in S2 is in the range of 120℃-150℃, and the drying time is 10min-30min; the washing between the two dryings is washed with clean water, and then squeezed in the range of 1kg-5kg, and the washing-squeezing operation is repeated 40-80 times.

9. The wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The structure comprises a base fabric, on the surface of which there is a polyurethane coating, the surface of the polyurethane coating has regular and orderly vertical bubbles to the inside, and the surface of the polyurethane coating without bubbles and the inner surface of the bubbles have a bridging organic silicone gel layer.

10. The wear-resistant and acid- and alkali-resistant CMP polishing pad with controllable pores according to claim 9, characterized in that: The thickness of the polyurethane coating is 0.6mm-0.7mm; The length of the pores is in the range of 0.3 mm to 0.7 mm; The bottom diameter of the pores is in the range of 0.09 mm to 0.3 mm.